PENGARUH AMPER TERHADAP CACAT LAS PADA PENGELASAN BAJA LUNAK DENGAN MENGGUNAKAN PENGELASAN SMAW POSISI PENGELASAN 2F - ADHIE SAPUTRA; Tuparjono; Sugiyarto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Abstract In the SMAW welding process, the problem of welding defects is still often found. This can be the result of using an improper welding ampere. In this study, welding testing was carried out by utilizing variations in the use of a welding amper according to the electrode diameter. The welding process uses low carbon steel St 37 with 2F welding joints. The electrode used was AWS A5.1 E6013 with a diameter of 3.2 mm with a variation of amperage 85, 95 and 115. From the experimental results, it was found that for Amperes 85, it was found that the porosity welding defect and the welding leg showed poor results with a thickness of 5.7 mm and at Amperes 115 welding results show uneven welds and weld feet show good results compared to amperage 85 and 95 with a thickness of 6.1 mm. Observation of the welding arc at times (seconds) 10, 13, 15 and 17 for the amperage used, namely 85, 95 and 115, is obtained, the amperage of 85 shows the phenomenon of the welding arc movement is not normal at 10 and 13 seconds, at that second the arc length height is more than normal, which is 5 mm and 4.9 mm, the resulting defect is porosity. At 15 and 17 seconds, there is no defect in the welds. Amper 95 and 115 show the phenomenon of normal welding arc movement at 10, 13, 15 and 17 seconds and no defects occur. Observation of the results of welds on the weld toe found that, in the three amperage variations, there was a phenomenon that was not asymmetrical as the weld toe. The welding feet are not as symmetrical as the welding speed is different at layers 2 and 3.